Assessing the Value of a Citizen Science Approach for Ctenophore Identification - Johansen, Ellie; Aberle, Nicole; Østensen, Mari-Ann; Majaneva, Sanna (Frontiers in Marine Science, 2021)
During the era of biodiversity loss, a complete species census and understanding where the different species occur is of high priority. Even though this knowledge has increased tremendously, mainly with expanded use of integrated taxonomic identification, there are groups where our knowledge is very limited, both in terms of diversity and distribution. Ctenophores are such a group. Due to a lack of identification literature, damage to specimens during net sampling and sample processing, difficulties with preservation and a considerably undescribed diversity within the phylum, this group is often hard to work with. A citizen science approach was applied during a mapping campaign on ctenophore diversity along the Norwegian coast in order to have a broad geographical coverage. This was achieved by a collaboration with five diving clubs along a south-north geographical gradient that were briefly introduced to ctenophore taxonomy and ecology and sampling techniques using Whatman® FTA® Cards. The data collected by the participating divers gave a broad spatial coverage and provided information on ctenophore diversity in these regions. The use of FTA® Cards in the sampling allowed successful species and genus level identification using DNA barcodes. However, small obstacles such as accurate morphological species identification and labor-intensive issues were identified that can impede the use of large-scale citizen science approaches to map ctenophore diversity and thus recommendations for future implications that address these issues are proposed here.